(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This work is about the record of an interview given by Profa. Dr. Ana Elvira Wuo, from the Federal University of Uberlândia (UFU). Ana Wuo is an important author and clownesse in the Brazilian context, standing out for her pioneering role in the Performing Arts from the creation of the concept “Clown Visitor”, coined in 1992. She is also a pioneer in academic research carried out by women clowns, a phenomenon which became popular in Brazil only in the 2010s, with Ana Wuo being one of the main references in the area.